Association between late bedtime and obesity in children and adolescents: a meta-analysis - Hu, Na; Wu, Ying; Yao, Qing; Huang, Shixiang; Li, Wen; Yao, Zhenhua; Ye, Chunfeng (Frontiers in Pediatrics, 2024)
Background: Short sleep duration has been related to obesity in children and adolescents. However, it remains unknown whether late bedtime is also associated with obesity and whether the association is independent of sleep duration. A meta-analysis was performed to address this issue.In order to accomplish the aim of the meta-analysis, a comprehensive search was conducted on databases including PubMed, Embase, and Web of Science to identify observational studies. The cutoff to determine late bedtime in children in this meta-analysis was consistent with the value used among the included original studies. As for obesity, it was typically defined as a body mass index (BMI) > 95th percentile of age and sex specified reference standards or the International Obesity Task Force defined age-and gender-specific cut-off of BMI. The Cochrane Q test was employed to evaluate heterogeneity among the included studies, while the I 2 statistic was estimated. Random-effects models were utilized to merge the results, considering the potential impact of heterogeneity.Results: Tweleve observational studies with 57728 participants were included.Among them, 6815 (11.8%) were obese. Pooled results showed that late bedtime reported by the participants or their caregivers was associated with obesity (odds ratio [OR]: 1.27, 95% confidence interval [CI]: 1.16 to 1.39, p < 0.001; I 2 = 0%). Subgroup analysis showed consistent results in studies with (OR: 1.33, 95% CI: 1.04 to 1.70, p = 0.02) and without adjustment of sleep duration (OR: 1.27, 95% CI: 1.14 to 1.41, p < 0.001). Further subgroup analysis also showed that the association was not significantly affected by study location, design, age of the participants, or diagnostic methods for obesity (p for subgroup difference all > 0.05).Late bedtime is associated with obesity in children and adolescents, which may be independent of sleep duration.